Dominican Dignitaries and Private Preaching at Papal Avignon. Part III: Conclusion - Beattie, Blake (Medieval sermon studies, 2019)
Private preaching certainly existed at papal Avignon, though a shortage of private sermon texts makes it difficult to gauge either the frequency with which it occurred or its importance to the cultural life of the fourteenth-century curia. The survival in a single manuscript of two sermons, preached by prominent Dominicans in the private chapel of Cardinal Pierre des Prés in the spring of 1340, may provide some insight in the phenomenon of private preaching at Avignon. Similar - not identical, but very similar - in structure, tone, and topoi to sermons preached before the popes during the solemn liturgies of the Avignonese chapel, the two private texts seem to suggest that private preaching at Avignon grew up in imitation of the liturgical sermons of the papal chapel, but without the ceremonial context.